Lung metastasectomy in adenoid cystic cancer: Is it worth it?. (February 2017) - Girelli, Lara; Locati, Laura; Galeone, Carlotta; Scanagatta, Paolo; Duranti, Leonardo; Licitra, Lisa; Pastorino, Ugo
Highlights: Delayed metastases occur in 25–50% of patients with adenoid cystic carcinoma (ACC). Pulmonary metastasectomy as a curative procedure in ACC should be further investigated. ACC has a tendency to local recurrence and long-term distant metastases. Lung resection for metastatic ACC is acceptable if complete resection is feasible. Symptomatic benefits of incomplete lung resection in ACC remain to be proven. Abstract: Background and purpose: Adenoid cystic carcinoma (ACC) of salivary glands is characterized by long-term distant metastasis, most commonly in lungs. No agreement has been reached about the role of surgical treatment of pulmonary lesions. We evaluated the long-term results of lung metastasectomy for ACC in order to identify factors that should be taken into account in selecting patients eligible for surgery and treatment planning. Patients and methods: A retrospective study was conducted on 109 patients selected from our institutional experience and from the International Registry of Lung Metastases. Survival was calculated by Kaplan-Meier estimate and prognostic factors endowed with a predictive power for most other metastatic cancers were investigated. Results: The cumulative survival was 66.8% at 5 years and 40.5% at 10 years. In patients with a disease-free interval (DFI) greater than 36 months, the overall survival was 76.5% at 5 years. Survival in case of complete surgical resection was 69.5% at 5 years. Multivariate analysis confirmed DFI and completeness of resection resulted in the best prognostic variables. Discussion: Lung metastasectomy should be considered as a therapeutic option to achieve local control of disease when 2 conditions are met: (1) complete surgical resection is feasible and (2) the time to pulmonary relapse after primary tumor treatment is greater than 36 months. Symptomatic benefits of an incomplete lung resection in slow-growing tumors such as ACC remain uncertain. The turning point in the management of disseminated cancers will be clarified with biological profiling of ACC and the development of targeted therapies.